Penilaian Bisnis dan Estimasi Nilai Intrinsik PT. Garuda Indonesia (Persero), Tbk saat Ipo Februari 2011 - Theresia Lesmana; Yen Sun (Bina Nusantara University, 2013)
Business valuation is an activity to estimate the value of company. The writers chose PT. Garuda Indonesia (Persero), Tbk. as the research object because PT. Garuda Indonesia (Persero), Tbk. just did an IPO on February 11, 2011. Based on IPO result, it is known the shares of PT. Garuda Indonesia (Persero), Tbk is overvalued to the intrinsic value. Therefore, the writers are interested in writing the thesis with title “BusinessValuation and Estimated Intrinsic Value of PT. Garuda Indonesia (Persero), Tbk when IPO on February 2011”. Business valuation used SWOT analysis and Porter analysis to know the non-financial performance. While from financial terms used Free Operating Cash Flow to the Firm (FCFF) to estimate the intrinsic value. Based on the analysis, it is obtained intrinsic value of share than compared with IPO price. The analysis used data from company website which was secondary data so that all necessary data in the research is available and could be accessed by everyone. The research approach used qualitative approach, by not using the hypothesis, and the result of reseacrh is descriptive data in the form of a narrative essay. Based on SWOT and Porter analysis, the company has good non-financial performance and is worth for investment options. Based on FCFF analysis, value of PT. Garuda Indonesia (Persero), Tbk. shares is overvalued. The writers advised stakeholders to not only see from overalued of shares but also see the non-financial performance.